Streptococcus mutans Displays Altered Stress Responses While Enhancing Biofilm Formation by Lactobacillus casei in Mixed-Species Consortium - Wen, Zezhang T.; Liao, Sumei; Bitoun, Jacob P.; De, Arpan; Jorgensen, Ashton; Feng, Shihai; Xu, Xiaoming; Chain, Patrick S. G.; Caufield, Page W.; Koo, Hyun; Li, Yihong (Frontiers in Cellular and Infection Microbiology, 2017)
Like Streptococcus mutans, lactobacilli are commonly isolated from carious sites, although their exact role in caries development remains unclear. This study used mixed-species models to analyze biofilm formation by major groups of oral lactobacilli, including L. casei, L. fermentum, L. rhamnosus, L. salivarius ssp. salivarius and L. gasseri. The results showed that lactobacilli did not form good biofilms when grown alone, although differences existed between different species. When grown together with S. mutans, biofilm formation by L. gasseri and L. rhamnosus was increased by 2-log (P<0.001), while biofilms by L. fermentum reduced by >1-log (P<0.001). L. casei enhanced biofilm formation by ~2-log when grown with S. mutans wild-type, but no such effects were observed with S. mutans deficient of glucosyltransferase GtfB and adhesin P1. Both S. mutans and L. casei in dual-species enhanced resistance to acid killing with increases of survival rate by >1-log (P<0.001), but drastically reduced the survival rates following exposure to hydrogen peroxide (P<0.001), as compared to the respective mono-species cultures. When analyzed by RNA-seq, more than 134 genes were identified in S. mutans in dual-species with L. casei as either up- or down-regulated when compared to those grown alone. The up-regulated genes include those for superoxide dismutase, NADH oxidase, and members of the mutanobactin biosynthesis cluster. Among the down-regulated genes were those for GtfB and alternative sigma factor SigX. These results further suggest that interactions between S. mutans and oral lactobacilli are species-specific and may have significant impact on cariogenic potential of the community.